2018
DOI: 10.1111/1346-8138.14462
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term safety and efficacy of continuous acitretin monotherapy for three children with different severe hyperkeratotic disorders in China

Abstract: Long-term systemic treatment with acitretin for severe hyperkeratotic disorders is needed to maintain quality of life of afflicted patients, but treatment has been limited owing to its potential side-effects including skeletal malformations, particularly for children during their growth and development. A retrospective investigation was conducted with three children afflicted with a severe hyperkeratotic disorder, namely Darier's disease, bullous ichthyosiform erythroderma or lamellar ichthyosis, who were cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Several studies observed that the patients in whom the treatment of retinoids was stopped too early/fast or the cumulative dose was too low showed an increased chance of wart recurrence and a decreased response to treatment 20,41,42 . In agreement with our previous studies on children with pustular psoriasis treated with acitretin ≤1 mg kg −1 day −1 for 3 months 43 and children with different severe hyperkeratotic disorders treated with acitretin 0.2‐0.3 mg kg −1 day −1 for more than 12 years, 44 no significant side effects were reported during the treatment and follow‐up of acitretin monotherapy apart from mild cheilitis, skin and mouth dryness, hair loss, and a slight increase in lipid levels in our study.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies observed that the patients in whom the treatment of retinoids was stopped too early/fast or the cumulative dose was too low showed an increased chance of wart recurrence and a decreased response to treatment 20,41,42 . In agreement with our previous studies on children with pustular psoriasis treated with acitretin ≤1 mg kg −1 day −1 for 3 months 43 and children with different severe hyperkeratotic disorders treated with acitretin 0.2‐0.3 mg kg −1 day −1 for more than 12 years, 44 no significant side effects were reported during the treatment and follow‐up of acitretin monotherapy apart from mild cheilitis, skin and mouth dryness, hair loss, and a slight increase in lipid levels in our study.…”
Section: Discussionsupporting
confidence: 90%
“…For instance, the initial dose of acitretin is 10 to 25 mg/day. 4,5 Provided no side effects are observed, the dose of acitretin can be gradually increased up to 60 mg/day within 2 months. After the lesions resolve, the dose of the remedy can be gradually reduced.…”
Section: Discussionmentioning
confidence: 99%
“…After the lesions resolve, the dose of the remedy can be gradually reduced. 4,6 T A B L E 1 Darier disease treatment…”
Section: Discussionmentioning
confidence: 99%
“…While there is no previously reported experience with the use of alitretinoin in children, systemic isotretinoin and acitretin have been prescribed for decades in paediatric dermatology for a number of dermatoses and prolonged treatment up to many years is regularly performed . Acitretin is even used in neonates with severe disorders of cornification such as harlequin‐ichthyosis .…”
Section: Discussionmentioning
confidence: 99%